The Relationship Between Self-Efficacy and Subjective Welfare of Adolescent Santri in Islamic Boarding Schools - Safera Dwi Intan Rahmawati; Hazim Hazim (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between self-efficacy and subjective well-being in adolescent students at Pondok An-Nur Sidoarjo. This type of research is quantitative correlational. The variables in this study are self efficacy (x) and subjective well being (y). The study was conducted at the An-Nur Islamic Boarding School, Sidoarjo with a population of 190 teenage students. a sample of 123 teenage students using simple random sampling. The data collection technique uses a psychological scale with a Likert scaling model, namely the self-efficacy scale and the subjective well-being scale. The hypothesis in this study is that there is a positive relationship between self-efficacy and subjective well-being in adolescent students at Pondok An-Nur Sidoarjo. Data analysis used product moment correlation technique with the help of SPSS 25 for windows program. The results of data analysis correlation value of 0.883 with a significance of 0.000 <0.05, meaning that there is a positive relationship between self-efficacy and subjective well-being in adolescent students at Pondok An-Nur Sidoarjo. The higher the self efficacy, the higher the subjective well being. On the other hand, the lower the self-efficacy, the lower the subjective well-being of adolescent students.